1980
DOI: 10.1097/00000658-198012000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Operative Risk Factors of Colon Resection in the Elderly

Abstract: Between January 1, 1974, and December 31, 1978, patients over 50 years of age underwent colon resections in three West Virginia Hospitals. The patients were studied by decades of age to compare the operative risks in younger and elderly patients. Preoperative assessments of cardiovascular, pulmonary, renal, hepatic, metabolic and nutritional states were compared with the postoperative morbidity and mortality rates. Complications occurred in 33% of all the patients who had resections, with 17 (4.8%) deaths. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

1983
1983
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(47 citation statements)
references
References 4 publications
0
43
0
4
Order By: Relevance
“…Weight loss and obstructive conditions were perceived to negatively impact short-term outcomes, as well as a number of medical conditions such as cardiovascular, pulmonary, renal, hepatic, and metabolic conditions [8][9][10][11].…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss and obstructive conditions were perceived to negatively impact short-term outcomes, as well as a number of medical conditions such as cardiovascular, pulmonary, renal, hepatic, and metabolic conditions [8][9][10][11].…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%
“…There is considerable evidence that this steadily expanding population receives substandard treatment when compared with younger age groups [4]. Possible explanations that have been suggested for this inequity in treatment include A) the perceived limitations to conventional treatments in the elderly [5,6]; B) concerns about attendant serious associated medical conditions [7,8], and C) a reluctance by clinicians to incorporate older patients either into clinical trials of novel agents or into existing screening programs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One series reported an incidence of 45% of patients 70 years and over and a 100% incidence in the 80 year and over group. 9 Boyd et al 2 in studying colon resection in the elderly reported cardiovascular disease in 57% of patients aged 70 to 79 years and in 85% of those 80 years and over.…”
Section: Major Complicating Systemic Diseases Cardiovascular Diseasementioning
confidence: 99%
“…2 These workers believe that the role of the complicating disease processes is more significant than increasing age.…”
Section: Increasing Agementioning
confidence: 99%
See 1 more Smart Citation